A second species of Apterodina (Chrysomelidae: Eumolpinae) from Ecuador - Flowers, R. Wills (Zootaxa, 2009)
The flightless genus Apterodina Bechyné is known from four South American species: two in southeastern Brazil and one each in Colombia and Ecuador (Flowers 2004). This paper describes a second Ecuadorian Apterodina and gives the first habitat data for this genus. Specimens are deposited in the following institutions: FSCA, Florida State Collection of Arthropods, Gainesville, Florida, USA; MECN, Museo Ecuatoriano de Ciencias Naturales, Quito, Ecuador.